HABITUS MASYARAKAT DI DAERAH KEKERINGAN PADA DESA JATISARI KABUPATEN SITUBONDO - Gusnia Ami Khumairo; Baiq Lily Handayani (Universitas Wijaya Kusuma Surabaya, 2022)
Drought is a serious problem that often arises when the dry season arrives. Usually, this situation occurs in an area that continuously experiences below-average rainfall so that the water supply becomes less. In general, the onset of a drought disaster cannot be known, but it can be said that drought occurs when the available water is no longer sufficient for daily needs. One example is the drought that occurred in Jatisari Village, Arjasa District, Situbondo Regency. The people of Jatisari Village have to try hard to get water that is used for their daily needs such as drinking, cooking, bathing, and washing. This study uses Pierre Bourdieu's theory of habitus. Habitus is the mental or cognitive structure by which people relate to the social world. This study uses qualitative research methods, with a focus on the ethnographic approach. Ethnography focuses on groups that share a common culture. The results of the research obtained are that the habitus in Jatisari Village makes the community have a helping nature as evidenced by the existence of mutual cooperation in making water sources and repairing damaged bore wells. Then there is harmony with neighbors when they are allowed to borrow water, entrusting the jurigen to fetch water, and the honesty of the community when conducting water transactions makes the relationship closer in society.Keywords: Adaptation to Climate Change, Drought, Habitus